Missing the Boat on Freshwater Fish Conservation in California. Issue 1 (1st July 2016) - Grantham, Theodore E.; Fesenmyer, Kurt A.; Peek, Ryan; Holmes, Eric; Quiñones, Rebecca M.; Bell, Andy; Santos, Nick; Howard, Jeanette K.; Viers, Joshua H.; Moyle, Peter B.
Abstract: Population growth and increasing water‐use pressures threaten California's freshwater ecosystems and have led many native fishes to the brink of extinction. To guide fish conservation efforts, we provide the first systematic prioritization of river catchments and identify those that disproportionately contribute to fish taxonomic diversity. Using high‐resolution range maps of exceptional quality, we also assess the representation of fish taxa within the state's protected areas and examine the concordance of high‐priority catchments with existing reserves and among distinct taxonomic groups. Although most of the state's native fishes are found within protected areas, only a small proportion of their ranges are represented. Few high‐priority catchments occur within protected areas, suggesting that fish conservation will require active management and targeted river restoration outside of reserves. These results provide the foundation for systematic freshwater conservation planning in California and for prioritizing where limited resources are allocated for fish recovery and protection.